Establishment of landslide early-warning indicator using the combination of numerical simulations and case matching method in wushan open-pit mine - Zhang, Penghai; Deng, Wenxue; Liu, Feiyue; Wang, He; Dong, Xin; Niu, Peng (Frontiers in Earth Science, 2022)
Landslides seriously threaten the safety of human life and property. In order to predict the on-set of potential landslides, this paper first characterizes the physical and mechanical parameters of rock mass on the basis of core rock quality designation identification, the geostatistics interpolation method, and the Hoek-Brown criterion. Then, the rock-mass physical and mechanical parameters characterization model was transformed to the slope numerical models, and the characteristics of potential landslides were predicted combined with the monitoring data and numerical simulation. Finally, on the basis of pairing between potential- and historical landslide cases, an early-warning indicator of a potential landslide was set as a posterior indicator of a historical landslide with the highest similarity. The results show that the potential landslide mode of the west and the southwest slope of the Wushan open-pit mine, the case study considered here, was a single-step wedge landslide and an integral-incline landslide. These two types of landslides were found to be most similar to those in the Anjialing open-pit mine and the Fushun West open-pit mine. Based on the posterior-warning indicator of the most similar landslide cases, the warning indicators of the west and southwest slope are set as 12.7 mm/d and 135.2 mm/d. The proposed method here provides a reference for the establishment of early-warning indicators for landslides in open-pit mines.